Propuesta de un modelo de gestión para la docencia: experiencia de una universidad estatal chilena (2020)
This article problematizes a relevant issue in higher education that understands teaching management as the ability to address the current requirements of university teaching activity in a professional context. To this end, and taking as reference the guidelines of a ministerial project, the proposal made in a Chilean state university is presented. According to the available information, teachers start a transition towards academic functions, taking into account the orientations of the three quality components: curricular management and teacher development, student's trajectory and teaching management and innovation. In the reference approach, the relationships between university teaching, curricular approach and teaching management are described. The methodological approach presents an idea of integration for the training activity through the problem to be solved and the procedure used, the achievements and lessons learned for teaching management. The experience demonstrates the results through a description of the proposal based on the two case examples. Based on these, the definition of innovation management and curricular quality assurance is discussed.